Paradoks Pembangunan Pariwisata Berkelanjutan di Taman Nasional Sebangau: Studi Kasus Kelurahan Kereng Bangkirai - Yonatan Ari Santoso; Arif; Gabriel Keintjem; Felicitya Navida (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to analyze the Paradox of Sustainable Tourism Development in Sebangau National Park (a case study in Kereng Bangkirai). Using a qualitative approach and case study design, data were collected through observation, in-depth interviews, and documentation. The results show an imbalance between the objectives of sustainable tourism development and their implementation in the field. Key findings point to several critical issues, including a lack of clarity regarding the Government Decree (KTT) from the Tourism Management Unit, which leads to weak institutional governance, ineffective communication and coordination between the government and local communities, limited supporting infrastructure, and underutilization of developed facilities. Furthermore, high kiosk rental costs and a lack of tourism promotion have reduced the effectiveness of local economic empowerment. This condition has resulted in decreased community participation in destination management. This study offers solutions by strengthening collaborative governance, improving coordination between stakeholders, and optimizing the roles of the community and government to achieve sustainable, participatory, and equitable tourism development.